Phosphorus Nutrition in Songpu Mirror Carp (Cyprinus carpio Songpu) During Chronic Carbonate Alkalinity Stress: Effects on Growth, Intestinal Immunity, Physical Barrier Function, and Intestinal Microflora - Ze Fan; Di Wu; Jinnan Li; Chenhui Li; Xianhu Zheng; Liansheng Wang (Frontiers in Immunology, 2022)
Carbonate alkalinity is a major environmental stress factor affecting aquatic feed configuration, which easily causes oxidative stress and hypoimmunity for fish. Hence, the purpose of the study is to assess the potential effect of phosphorus on growth, intestinal oxidation resistance, physical barrier function, and microflora for Songpu mirror carp (Cyprinus carpio Songpu) (initial average weight of 2.95 ± 0.21 g) reared at the high-concentration carbonate alkalinity environment. A two-factor, three-level (2 × 3) design was applied, in which diets with three different phosphorus levels (3.6, 7.0, and 10.5 g/kg dry matter) were randomly assigned to 0 and 15 mmol/L carbonate alkalinity groups with three replicate aquariums. After the 8-week trial, we found that weight gain rate (WGR), specific growth rate (SGR), protein efficiency ratio (PER), and lipase and amylase activities in the intestine significantly (p < 0.05) declined with increasing carbonate alkalinity. Carbonate alkalinity of 15 mmol/L significantly reduced glutathione peroxidase (GSHPx) activities in the intestine (p < 0.05). The relative expressions of nuclear factor (erythroid-derived 2)-like 2 (Nrf2), glutathione peroxidase 1a (GPX1a), Clautin3, Clautin11, and tumor necrosis factor β (TNF-β) in the intestine were markedly downregulated by increasing carbonate alkalinity levels (p < 0.05), whilst the relative expressions of interleukin 1β (IL-1β) and tumor necrosis factor α (TNF-α) in the intestine were markedly upregulated (p < 0.05). At the 15 mmol/L carbonate alkalinity treatment, Songpu mirror carp suffer from hypoimmunity status with failed digestion, antioxidant, inflammation, and immune response, thereby inducing impaired growth. Additionally, significant increments in the abundance of Proteobacteria and a significant decrease in the abundance of Fusobacteria and the Firmicutes/Bacteroidetes ratio were caused due to excessively high carbonate alkalinity (15 mmol/L) and excessively low dietary phosphorus supply (3.6 g/kg). Collectively, 7.0 g/kg dietary phosphorus supplementation was effective in promoting intestinal antioxidant enzyme activities and the corresponding gene expression via the Keap1-Nrf2 signaling pathway and in enhancing intestinal immunity by upregulating anti-inflammatory and downregulating pro-inflammatory genes. Appropriate dietary phosphorus supply could promote the formation of beneficial microflora in freshwater, and it has the potential ability to transfer the adverse effect of carbonate alkalinity stress to the structural composition of intestinal microflora. Hence, consideration should be given to suitable phosphorus supply for fish under the chronic carbonate alkalinity stress.